2013
DOI: 10.1186/1745-6215-14-253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of periodontal treatment on the clinical parameters of patients with rheumatoid arthritis: study protocol of the randomized, controlled ESPERA trial

Abstract: BackgroundRheumatoid arthritis (RA) is a chronic inflammatory disorder that leads to joint damage, deformity, and pain. It affects approximately 1% of adults in developed countries. Periodontitis is a chronic oral infection, caused by inflammatory reactions to gram-negative anaerobic bacteria, and affecting about 35 to 50% of adults. If left untreated, periodontitis can lead to tooth loss. A significant association has been shown to exist between periodontitis and RA in observational studies. Some intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 39 publications
3
29
0
1
Order By: Relevance
“…A recent systematic review concluded that non‐surgical periodontal therapy in patients with RA with periodontal disease could result in reductions of ESR, without a significant effect on the RF or CRP levels . Non‐surgical mechanical therapy followed by systemic antibiotics led to improved clinical outcomes in patients with active RA . As mentioned above, the systemic characteristics of the included patients (baseline DAS28 scores, duration and type of drug therapy in patients with RA), as well as the severity of periodontitis, could explain the discrepancy with the studies that reported systemic improvements after periodontal therapy.…”
Section: Discussionmentioning
confidence: 93%
“…A recent systematic review concluded that non‐surgical periodontal therapy in patients with RA with periodontal disease could result in reductions of ESR, without a significant effect on the RF or CRP levels . Non‐surgical mechanical therapy followed by systemic antibiotics led to improved clinical outcomes in patients with active RA . As mentioned above, the systemic characteristics of the included patients (baseline DAS28 scores, duration and type of drug therapy in patients with RA), as well as the severity of periodontitis, could explain the discrepancy with the studies that reported systemic improvements after periodontal therapy.…”
Section: Discussionmentioning
confidence: 93%
“…Also, polysaccharide A produced by B. fragilis binds TLR‐2 on the surface of lymphocytes and DCs. It thus promotes the maturation of CD4 + lymphocytes into T reg lymphocytes and the production of anti‐inflammatory cytokines such as IL‐10 . Rogier et al .…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…110 More recent treatment studies confirm these findings, with a significant decrease in TNF-a levels. [119][120][121] Improvement in signs and symptoms of RA occurred, regardless of whether the RA patients were under anti-TNF-a treatment. 117 Anti-TNF-a RA treatment had no effect on the periodontal health without periodontal therapy.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%